Acute psychosis due to brucellosis in a rural Iran: a report of two cases - Bidaki, R; Yassini, SM; Maymand, MT; Mashayekhi, M; Yassini, S (International Journal of Infection and Microbiology, 2013)
Introduction: Brucellosis is a zoonotic disease that causes multi systemic involvement. Neurobrucellosis occurs in less than 5% of patients. Psychosis as a presentation of neuro-brucellosis is a rare condition. Case Report: We report a woman that was referred because of psychotic depression following brucellosis. Also we present a 66-year-old man that was admitted because of acute psychotic symptoms. He had behavioral disorders, visual and auditory hallucination, restlessness, impulsivity, incoherency and episodic crying. Neurobrucellosis was confirmed. Conclusion: In patients with atypical psychosis in endemic areas, physicians should consider the portability of brucellosis. DOI: http://doi.dx.org/10.3126/ijim.v2i1.8007 Int J Infect Microbiol 2013;2(1):29-31